2020
DOI: 10.2991/dsahmj.k.200220.001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Bacteria associated with Urinary Catheters from Patients Suffering from Urinary Tract Infections

Abstract: Urinary catheters act as a reservoir of resistant pathogens. Several factors (type, duration, procedural mistakes during insertion of catheter, associated diseases of patients, etc.) are responsible for the different catheter-associated urinary tract infection (CAUTI) rates in different healthcare setups. This study was conducted to determine bacteria that can be found in the urinary catheter of UTI patients. The samples were aseptically collected into a sterile container 48 h after insertion of catheter. Urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The findings of a similar study performed by Bashir and colleagues (2020) highlighted that most widespread bacteria were the gram-negative namely E.coli, Proteus mirabilis, K.pneumoniae, Proteus vulgaris, and P.aeruginosa while gram+ve bacteria were S.aureus and S.saprophyticus. 7 When the resistance pattern of organisms were evaluated, study indicated that Escherichia coli was mostly sensitive (>85%) to Meropenem 20 A study conducted by Kazi and partners (2015) asserted that Pseudomonas was the most resistant uropathogen that showed an elevated resistance to several antibiotics including meropenem and imipenem. 1 A most recent study conducted by Ejerssa and companions (2021) reported that >70% of uropathogens were sensitive to gentamicin, chloramphenicol, amikacin and nitrofurantoin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of a similar study performed by Bashir and colleagues (2020) highlighted that most widespread bacteria were the gram-negative namely E.coli, Proteus mirabilis, K.pneumoniae, Proteus vulgaris, and P.aeruginosa while gram+ve bacteria were S.aureus and S.saprophyticus. 7 When the resistance pattern of organisms were evaluated, study indicated that Escherichia coli was mostly sensitive (>85%) to Meropenem 20 A study conducted by Kazi and partners (2015) asserted that Pseudomonas was the most resistant uropathogen that showed an elevated resistance to several antibiotics including meropenem and imipenem. 1 A most recent study conducted by Ejerssa and companions (2021) reported that >70% of uropathogens were sensitive to gentamicin, chloramphenicol, amikacin and nitrofurantoin.…”
Section: Discussionmentioning
confidence: 99%
“…Though, utilizing catheter for >2 days could be an important factor regarding CAUTI. 7 The infectivity is noticed among 10 to 50 percent patients with temporary catheterization, however, if not treated, it can cause severe complications for example, septicemia, sepsis, pyelonephritis and bacteremia that accounts for considerable morbidity as well as mortality related to CAUTIs. 8 The bacterial species for example, E.coli, Staphylococcus, Pseudomonas aeruginosa, Proteus vulgaris, Klebsiella, Proteaus mirabilis, fungal and enterococcal species can lead to CAUTIs.…”
Section: Introductionmentioning
confidence: 99%
“…It exposed that about 50% of females have experienced a UTI at least once throughout their lifespan (20). It is thought that a high risk of women for UTI than men due to their physiological and anatomical characteristics (21). For instance, the closeness between the urethra/anus and the genital tract in females is one possible reason that could enhance the auto-transmission of the bacteria and increase the rate of UTIs in females (22).…”
Section: Discussionmentioning
confidence: 99%
“…It revealed that about 50% of women experience at least one episode of UTI at some point in their lifetime 26 . It is supposed that women are at high risk for UTI compared to men due to their anatomical and physiological characteristics 27 . For example, the proximity between the genital tract and the urethra/anus in women is one potential reason that could facilitate the auto-transmission of the pathogens and lead to increasing the rate of UTIs in women 28 .…”
Section: Discussionmentioning
confidence: 99%